2003
DOI: 10.1080/0960312031000102859
|View full text |Cite
|
Sign up to set email alerts
|

Coping with hygiene in South Africa, a water scarce country

Abstract: The burden of infectious diseases may be reduced by adopting effective infection control measures. Some of these are dependent on the provision of adequate and safe water supplies for maintenance of basic standards of personal, domestic and healthcare hygiene. Consequences of scarce, and sometimes unsafe, waters supplies in South Africa are highlighted with reference to healthcare-associated infections, community acquired infectious intestinal diseases and domestic practices as infection sources. Availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…Previous studies conducted in Ilorin, Abeokuta, in Nigeria and Accra in Ghana, respectively, showed similar trend [2, 16, 17]. This was, however, not the case in studies conducted in South Africa and Kenya, respectively, where street food vendors were mostly males [18, 19]. Gender role in socioeconomic development is often influenced by cultural orientation and varies from one geographical location to another.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies conducted in Ilorin, Abeokuta, in Nigeria and Accra in Ghana, respectively, showed similar trend [2, 16, 17]. This was, however, not the case in studies conducted in South Africa and Kenya, respectively, where street food vendors were mostly males [18, 19]. Gender role in socioeconomic development is often influenced by cultural orientation and varies from one geographical location to another.…”
Section: Discussionmentioning
confidence: 87%
“…The provision of drinking water of adequate quality and quantity remains a major public health need in many African countries where diarrhoeal diseases continue to cause extensive morbidity and mortality. The burden of infectious disease may be reduced by adopting effective control measures; some of these are dependent on the provision of adequate and safe water supplies for basic standards of personal domestic and health care hygiene (Duse et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The provision of drinking water of adequate quality and quantity remains a major public health need in many African countries, where diarrhoeal diseases continue to cause extensive morbidity and mortality [1]. In recent years, there has been a large movement of internally displaced people into the peripheral areas of Nyala city because of the civil war in Darfur region.…”
Section: Introductionmentioning
confidence: 99%